2022
DOI: 10.1177/17474930221086417
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and mortality of cerebrovascular disease in Spain: 1,600,000 hospital admissions between 2001 and 2015

Abstract: Background: To analyze the incidence and mortality of cerebrovascular diseases (CeVD) in Spain from 2001 to 2015. Methods: Retrospective study of hospital incidence, hospital case-fatality and population mortality, with records from the Spanish Government Statistics. Days of hospital stay and risk of death during admission (RD) were estimated adjusting for age, sex, first stroke (FS), atrial fibrillation (AF), diabetes, hypertension, and smoking. Results: There were 1,662,487 stroke cases older than 15 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…A further paper in this month’s issue analyzed the incidence and mortality of cerebrovascular disease in Spain from 2001 to 2015. 4 Reassuringly, it was found that stroke mortality reduced by half in Spain over this period, consistent with many studies from other high-income countries. 5 These show that a combination of public health measures, and better primary prevention, can reduce incidence of stroke and cardiovascular disease and emphasises the importance of developing such approaches globally, including in LMIC.…”
supporting
confidence: 85%
“…A further paper in this month’s issue analyzed the incidence and mortality of cerebrovascular disease in Spain from 2001 to 2015. 4 Reassuringly, it was found that stroke mortality reduced by half in Spain over this period, consistent with many studies from other high-income countries. 5 These show that a combination of public health measures, and better primary prevention, can reduce incidence of stroke and cardiovascular disease and emphasises the importance of developing such approaches globally, including in LMIC.…”
supporting
confidence: 85%